Implementation Of Security Information And Event Management (Siem) In Monitoring Networks At SMA 1 Muhammadiyah Boarding School - Paw, M. Reyza Putra; Aspriyono, Hari; Akbar, Abdussalam Al (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2024)
Implementation of Security Information Event Management (SIEM) for Network Monitoring at SMA Muhammadiyah Boarding School can help network administrators know the activity and status of devices connected to the network whether UP or Down, can help provide information in the form of logs of services that run and log security events on each device connected to the network. This of course can make it easier for network administrators to deal with problems found on network devices connected to OSSIM AlienVault. In OSSIM AlienVault there is a web UI platform that can make it easier for network administrators to monitor the network at SMA Muhammadiyah Boarding School. Where the OSSIM AlienVault Web UI can be accessed via the IP Address Server in the browser. Based on the tests carried out, the results show that the Implementation of Security Information Event Management (SIEM) for Network Monitoring at SMA Muhammadiyah Boarding School runs well and can help network administrators in network monitoring and can provide information in the form of event logs on each device connected to the network.